Design of Medicine Inventory System - Kartikasari, Maya Andini (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The efficient management of medicine inventory is crucial for the smooth operation of pharmacies, ensuring the availability of essential medications while minimizing excess stock and wastage. This research presents the design of a Medicine Inventory System which is recommended to be implemented at Yasmin Raya Pharmacy, aimed at optimizing inventory tracking, stock replenishment, and overall operational efficiency. The proposed system integrates real-time inventory monitoring, automated stock updates, and alerts for medication expiry, addressing common challenges faced by the pharmacy in managing its stock manually. The methodology used is the use case diagram, sequence diagram and prototype model.